The Impact of Unethical AI Use on Academic Writing Regression: Case Study of English Students at PSDKU Aru - Aritonang, Parjolo; Toisuta, Emanuela Giovanni (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2025)
This qualitative case study investigates how unethical AI tool usage contributes to the regression of academic writing skills among 20 English students at PSDKU Aru, Maluku, Indonesia. Data was collected through writing samples, plagiarism reports, interviews, and longitudinal grade tracking over six months. Findings reveal that students engaging in uncritical copy-pasting of AI-generated content (e.g., ChatGPT, Gemini) exhibited significant declines in paragraph coherence, argumentative depth, and syntactic complexity. Key regression patterns included fragmented topic sentences, incohesive supporting evidence, and formulaic conclusions. The study highlights ethical and pedagogical implications, advocating for AI literacy integration and scaffolded writing assessments. Recommendations emphasize proactive policy reforms and metacognitive training to mitigate skill atrophy.